2013
DOI: 10.1021/ja406300c
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Labile Zn Sites in Drug-Target Proteins

Abstract: Labile Zn fingers (Zfs) in proteins contain Zn-bound thiolates that can react with electrophilic agents, causing Zn(2+) ejection and protein unfolding. Such labile Zfs have been shown to be Cys4 or Cys3His cores whose Zn-bound Cys have no hydrogen bonds. Our aim here is to identify labile Zfs in proteins that are promising drug targets using these features. To prove the strategy used, we showed that five proteins with predicted labile Zfs reacted with Zn-ejecting agents, whereas five proteins with no or inert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…We then used these guidelines to identify drug-target proteins containing labile structural Zn-sites. 8,10 To circumvent toxicity due to undesirable targeting of essential human proteins, we had proposed using clinically safe (FDA-approved or in phase II/III clinical trials) Zn-ejecting agents that do not affect crucial host proteins (ESI Table S1 †) to target putative labile Zn-sites in viral proteins. 8 We showed that disulram, an anti-alcoholism drug, can eject Zn 2+ from the predicted labile Zn-Cys 4 site in the hepatitis C virus NS5A protein, inhibiting viral replication, and that inhibition was enhanced when disulram was combined with interferon-a.…”
mentioning
confidence: 99%
“…We then used these guidelines to identify drug-target proteins containing labile structural Zn-sites. 8,10 To circumvent toxicity due to undesirable targeting of essential human proteins, we had proposed using clinically safe (FDA-approved or in phase II/III clinical trials) Zn-ejecting agents that do not affect crucial host proteins (ESI Table S1 †) to target putative labile Zn-sites in viral proteins. 8 We showed that disulram, an anti-alcoholism drug, can eject Zn 2+ from the predicted labile Zn-Cys 4 site in the hepatitis C virus NS5A protein, inhibiting viral replication, and that inhibition was enhanced when disulram was combined with interferon-a.…”
mentioning
confidence: 99%
“…via its zinc-finger like motif, we tested three covalent inhibitors with thiol-reactive groups. Ebselen, disulfiram and auranofin have the potential to interact with zinc fingers, including via zinc ejection with consequent protein destabilization [69,70,79,80]. Both ebselen and auranofin are reported have some antimicrobial properties [81], ebselen is in clinical trials for a variety of conditions, ranging from stroke to bipolar disorder [82], and auranofin is used for treatment of rheumatoid arthritis [83].…”
Section: Discussionmentioning
confidence: 99%
“…In addition we found that dithiopyridine, an inhibitor of ZBTB25, blocked the recruitment of HDAC1 silencing complex to IL-12B promoter. Dithiopyridine is a zinc ejector that inactivates the functionality of zinc finger domain (Lee et al, 2013), and has been used for the inactivation of the zinc-finger nucleocapsid of HIV-1 (Arthur et al, 1998). We further found that knocking down of ZBTB25 disrupts the recruitment of HDAC1 to the promoter of IL-12B promoter and subsequently derepressing the gene expression.…”
Section: Discussionmentioning
confidence: 99%